HUBUNGAN KEPUASAN KERJA DENGAN KINERJA DAN PROFESIONALISME DENGAN KINERJA EDITOR JURNAL ILMIAH : (Studi Editor Jurnal Ilmiah di Universitas Negeri Malang) - Arif Andoyo; Sholihah Qomariyatus; Hidayati Firda (Jurnal Administrasi Publik, 2023)
The research was carried out from January to April 2022 at Universitas Negeri Malang aims to find a relationship between professionalism and performance, job satisfaction and performance. The population is 634 people, sample is 88 people. In collecting cross-sectional data was used explanatory survey method, primary and secondary data sources. Samples with probability sampling used simple random sampling. The results showed that professionalism had a positive and quite strong relationship performance, and correlation coefficient (r = 0.596) with significance 0.000 was obtained. Job satisfaction is positively related (unidirectional) and quite strong with performance, obtained a correlation coefficient (r = 0.580) with significance 0.000. If professionalism increases followed by increased performance, job satisfaction increases then performance will increase, conversely decreasing professionalism and job satisfaction will be followed by decrease in performance of scientific journal editor.